-2(5s-5)-10=-2(9s+10)-3

Simple and best practice solution for -2(5s-5)-10=-2(9s+10)-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(5s-5)-10=-2(9s+10)-3 equation:


Simplifying
-2(5s + -5) + -10 = -2(9s + 10) + -3

Reorder the terms:
-2(-5 + 5s) + -10 = -2(9s + 10) + -3
(-5 * -2 + 5s * -2) + -10 = -2(9s + 10) + -3
(10 + -10s) + -10 = -2(9s + 10) + -3

Reorder the terms:
10 + -10 + -10s = -2(9s + 10) + -3

Combine like terms: 10 + -10 = 0
0 + -10s = -2(9s + 10) + -3
-10s = -2(9s + 10) + -3

Reorder the terms:
-10s = -2(10 + 9s) + -3
-10s = (10 * -2 + 9s * -2) + -3
-10s = (-20 + -18s) + -3

Reorder the terms:
-10s = -20 + -3 + -18s

Combine like terms: -20 + -3 = -23
-10s = -23 + -18s

Solving
-10s = -23 + -18s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '18s' to each side of the equation.
-10s + 18s = -23 + -18s + 18s

Combine like terms: -10s + 18s = 8s
8s = -23 + -18s + 18s

Combine like terms: -18s + 18s = 0
8s = -23 + 0
8s = -23

Divide each side by '8'.
s = -2.875

Simplifying
s = -2.875

See similar equations:

| 3c=2c+17 | | s-2=5-s | | Y=-0.02x^2+.5x | | 7q+2(3-2w)=4(w+2)-(w-6) | | 2(4-4)+32= | | 2y=3y-13 | | 5(y-2)-2=(y+1)-5 | | 97/5-x/5=2.6 | | 6a=a+5 | | 2.5x=-20 | | 12x+3=8x+43 | | 18u+3=10u | | -39=1-5(-7) | | 4x-5y-5=0 | | 14d=10d+12 | | 8x+y=177 | | 97-x/5=2.6 | | Y=-0.02x^2+.5 | | 6x+4.5y=50 | | 8x-6=5x-10 | | 10x×1/5 | | 3+3(a+2)= | | (3+3i)(2-3i)= | | 2.5x(2.5x)+3x=2 | | -7x-129=113+4x | | 2s=s+16 | | 5x(5x)+3x=2 | | 5x+2y-5z=16 | | X=ln(3x) | | 3(a+1)-5=3a-4 | | -s=x-5 | | -96-11x=2x+151 |

Equations solver categories